Charge Decoupling and Its Effect on Energy Release and Transmision for One Dynamite and Water Gel Explosive - Calvin J. Konya; Robert Briton; S Lukovic (International Society of Explosives Engineers, 1987)
Investigators have reported that charges which are decoupled from the borehole wall produce different fragmentation then those which are fully coupled. The difference in effect could be as a result of energy doss during transmission across the air gap or it could be due to the change in detonation characteristics of the explosive as a result of the change in confinement on the charge during detonation. In order to better understand the phenomena of decoupling, a research project was conducted at the United States Bureau of Mines Station, near Pittsburgh, Pennsylvania. It was decided to use shock and bubble energy tests along with simultaneous velocity measurement to determine the mechanics of decoupling and energy transmission. Two explosives were selected for the test, one dynamite and one water gel. Test results indicated that decoupling could both boost the total energy output of the explosive and that further decoupling would drop the energy output.